PEMBINAAN PERKEMBANGAN KEBERAGAMAAN ANAK USIA DINI - Asnelly Ilyas (Ta'dib, 2009)
Among potentials that children have as they were born, religious potential is one that needs to be developed in line with other potentials by means of education. Pre-school aged children refer to those who are between 0 and 6 years old. They are in their ultimate growing and developing period in intelligence, emotion, social, and language. Specifically, characteristics of religious awareness among children is reflected in the form of unreflective, egocentrical, antropomorphical, vebal, ritual and imitative. Introducing and familiarizing religious among children can be done by making use of their initial growth and developing through good model, stories, field trip to behold the great and glory of Allah, to get used to worship, good moral, help each other, and so on. It is believed that introducing religion in early ages will provide children with guidance and foundation in their life.Kata Kunci: anak usia dini, pertumbuhan, perkembangan, keberagamaan